Health Education using Leaflet Media about Multidrug-Resistant Tuberculosis (MDR-TB) Improves Knowledge of Patients with Pulmonary Tuberculosis. - taurina, s; Puspitasari, Mellya (Adult Health Nursing Journal, 2024)
Introduction: Mycobacterium Tuberculosis germ resistance is a condition where Anti-Tuberculosis Drugs (OAT) are unable to kill Mycobacterium Tuberculosis germs. One type of resistance is Multidrug Resistant Tuberculosis. The consequences of being resistant to OAT are worsening health, increased costs, longer treatment, high rates of therapeutic failure and death.  Objectives: This study aims to analyse the effect of education about Multidrug-Resistant Tuberculosis (MDR-TB) with leaflet media on the level of knowledge of pulmonary tuberculosis patients at the Kanigaran Health Centre, Probolinggo City. Methods: This study used a Quasi-Experimental research design with a Pretest-Posttest with Control Group research design. The sample of this study was 60 people consisting of 30 Intervention groups and 30 Control groups with Purposive Sampling technique. Measurement of knowledge level using a questionnaire with 20 questionsThis study used the Wilcoxon test. Results: Pretest level of knowledge of respondents in the Intervention group in the Good category, namely 4 people (13.3%), posttest increased to 27 people (90.0%). Pretest level of knowledge of respondents in the Control group in the category of Less as many as 23 people (76.7%) and Posttest 24 people (80%). The Wilcoxone test found differences in Pre-test and Post-test knowledge in the Intervention and Control groups, namely P value 0.000 <0.05. Conclusions: There is an effect of education about Multidrug-Resistant Tuberculosis (MDR-TB) with leaflet media on the level of knowledge of pulmonary tuberculosis patients at Kanigaran Health Centre, Probolinggo City.